Iron and manganese as dopants used in the crystallization of highly resistive HVPE-GaN on native seeds. (22nd May 2019) - Iwinska, Malgorzata; Zajac, Marcin; Lucznik, Boleslaw; Fijalkowski, Michal; Amilusik, Mikolaj; Sochacki, Tomasz; Litwin-Staszewska, Elzbieta; Piotrzkowski, Ryszard; Grzegory, Izabella; Bockowski, Michal
Abstract: An influence of doping with iron and manganese on GaN crystallized by halide vapor phase epitaxy is described in this work. This is a continuation of previous work where solid iron was used as a metal precursor and semi-insulating GaN co-doped with manganese and iron was crystallized. In this paper, metals of the highest purity were used. The acceptors (iron and manganese) were incorporated separately in order to compensate unintentional donors present in undoped GaN crystals. Native GaN wafers were used as seeds. The crystallized doped samples were examined in terms of their structural and electrical properties. Concentrations of dopants and unwanted impurities were determined. Iron-doped and Mn-doped GaN, with resistivity at room temperature exceeding 10 7 Ωcm, was presented and compared. It was shown that, at room temperature, for the same acceptor concentration, GaN:Mn crystals present better structural quality and higher resistivity than GaN:Fe.